2020
DOI: 10.11604/pamj.2020.36.81.23776
|View full text |Cite
|
Sign up to set email alerts
|

Implications of COVID-19 infections in sickle cell disease

Abstract: Sickle cell disease is a major concern of public health significance in Africa. Nearly 2/3 rd of the global burden of sickle cell disease (SCD) is found to be in sub-Saharan Africa. There is increased mortality risk in sickle cell disease patients in Africa due to associated complications such as acute chest syndrome, asthma, pulmonary emboli and sepsis. Sickle cell disease management is the major contributor of financial burden on the government. Moreover, there is a shortage of medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The decreased effect of serum cytokines is one of the side effects of COVID-19 in some of them (15). Mortality from COVID disease is higher in patients with sickle cell disease and chronic respiratory or cardiovascular disease and hypertension than in patients with sickle cell disease alone (16). Examination of blood cells in patients with COVID-19 and sickle cell anemia revealed that all blood cells were stable, and only white blood cells were reduced.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The decreased effect of serum cytokines is one of the side effects of COVID-19 in some of them (15). Mortality from COVID disease is higher in patients with sickle cell disease and chronic respiratory or cardiovascular disease and hypertension than in patients with sickle cell disease alone (16). Examination of blood cells in patients with COVID-19 and sickle cell anemia revealed that all blood cells were stable, and only white blood cells were reduced.…”
Section: Resultsmentioning
confidence: 99%
“…Complications of sickle cell disease are permanent and temporary defects of the immune system, and the main symptom is fever. Every patient with this symptom should also be screened for COVID-19, regardless of whether they are exposed to the Coronavirus (16).…”
Section: Resultsmentioning
confidence: 99%
“…In some cases, even individuals with sickle cell trait are considered to be at risk ( 40 , 110 , 112 , 119 ). The immunosuppressive state, increased risk of sepsis, endothelial dysfunction, and cardiovascular impairment are some of the characteristics of sickle cell disease that may explain these outcomes ( 2 , 51 , 54 , 61 , 63 , 66 , 68 ). The fact that COVID-19 acts as a trigger for the occurrence of sickle cell complications, which are events that are associated with high mortality, may also contribute to this scenario, as will be discussed in the next section.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, patients with pre-existing medical conditions have a higher risk, both for contracting the virus and for developing severe complications from the infection. This is particularly true for patients living with NCDs such as Hypertension, Diabetes, heart disease, cancer and sickle cell disorder (SCD), who often have a compromised respiratory system (John and John 2020).…”
Section: Background Of Studymentioning
confidence: 99%
“…Nigeria has the largest burden of SCD globally with an estimated 150,000 babies born annually with the condition (Akodu et al, 2013). It is therefore a major concern as patients living with SCD are immunocompromised and at risk of suffering from chronic or acute complications due to COVID which may require urgent hospitalisation and intensive care (John and John 2020).…”
Section: Background Of Studymentioning
confidence: 99%